2020
DOI: 10.1136/bcr-2020-235608
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-associated lactic acidosis: reinforcing learning points

Abstract: Metformin-associated lactic acidosis (MALA) carries a high mortality rate. It is seen in patients with type 2 diabetes on metformin or patients who attempt suicide with metformin overdose. We present the case of a man in his early 20s with type 2 diabetes, hypertension and hypothyroidism who presented with agitation, abdominal pain and vomiting after ingesting 50–60 g of metformin; he developed severe lactic acidosis (blood pH 6.93, bicarbonate 7.8 mEq/L, lactate 28.0 mEq/L). He was managed with intravenous 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Previous studies have showed that people with chronic diseases such as T2DM often experience depression and anxiety, which can lead to suicidal behavior ( Semenkovich et al, 2015 ; Kim et al, 2022 ). Risky drugs include high doses of insulin, metformin, glipizide, liraglutide and sitagliptin ( Sarkar and Balhara, 2014 ; Goonoo et al, 2020 ; Tuncali et al, 2021 ). Our case further indicated that vildagliptin is also a potential drug for suicide and self-harm, which should be particularly noted in depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that people with chronic diseases such as T2DM often experience depression and anxiety, which can lead to suicidal behavior ( Semenkovich et al, 2015 ; Kim et al, 2022 ). Risky drugs include high doses of insulin, metformin, glipizide, liraglutide and sitagliptin ( Sarkar and Balhara, 2014 ; Goonoo et al, 2020 ; Tuncali et al, 2021 ). Our case further indicated that vildagliptin is also a potential drug for suicide and self-harm, which should be particularly noted in depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin-associated lactic acidosis is a rare complication of metformin treatment of type 2 diabetes, which can be caused due to take in large amount of the drug, or it can be provoked comorbidities such as renal or hepatic insufficiency or acute infection. Clinically, MALA can be presented with gastrointestinal symptoms (nausea, vomiting and diarrhea), altered mental status, hypotension and hypothermia [1]. In patients with hemodynamic instability due to septic shock and MALA, continuous renal replacement therapy (CRRT) has been reported to be successful.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycaemia and less commonly hyperglycaemia have also been reported in patients with acute metformin overdose. (7,8,9,10) MALA is a well-recognized, potentially fatal, rare adverse effect that is reported in acute overdose (11,12,13). MALA has also been described in patients with acute on chronic metformin toxicity, end stage renal disease and in patients with acute renal failure on chronic metformin therapy (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…(7,8,9,10) MALA is a well-recognized, potentially fatal, rare adverse effect that is reported in acute overdose (11,12,13). MALA has also been described in patients with acute on chronic metformin toxicity, end stage renal disease and in patients with acute renal failure on chronic metformin therapy (13,14). Its incidence varies from 3 to 10 per 100 000 patients (11,14,15,16).…”
Section: Introductionmentioning
confidence: 99%